Cell [videorecording (DVD)] - Alleca, Adam, 1983-; Cusack, John, 1966-; Jackson, Samuel L.; Keach, Stacy; Fuhrman, Isabelle, 1997-; Zarvos, Marcelo; Craycroft, Jacob; Simmonds, Michael; King, Stephen, 1947- (Lionsgate, 2016)
An apocalyptic thriller about a mysterious signal that reprograms the minds of cellphone users around the globe.